Impact Of Information Technology On Tax Administration In Southwest, Nigeria - Olatunji, Olaoye Clement; Ayodele, Kehinde Busayo (Archives of Business Research, 2017)
This study examined the impact of information technology on tax administration in south west, Nigeria. It specifically investigated the effect of information technology on tax productivity and the relationship between information technology on tax implementation and tax planning. Descriptive research design was employed, of which questionnaire was used to gather data and analysed with multiple regression and pearson product moment correlation. The study revealed that information technology (Online Tax Filing-OTF, Online Tax Registration-OTR and Online Tax Remittance-OTRE) affect tax productivity with -1.9%, 7.3% and 31.5% (p=0.85, 0.526 and 0.00), there is relationship of -5.9% (p=0.520), 9.7% (p=0.290) and 0.344 (p=0.000) between OTF, OTR and OTRE on Tax Implementation-TAXIMP and -3.8% (p=0.684), 14% (p=0.140) and -0.190 (p=0.038<0.05) relationship between OTF, OTR and OTRE on Tax Planning-TAXPLNN. The study concluded that information technology enhance the level of tax productivity and administration. It is therefore recommended that the respective agencies (federal, state and local government) responsible for tax collection should carry out one on one awareness in the form of seminars and sensitization of the process and suitability of information technology on tax administration.